2017
DOI: 10.1089/adt.2017.821
|View full text |Cite
|
Sign up to set email alerts
|

When Enough Is Enough: Decision Criteria for Moving a Known Drug into Clinical Testing for a New Indication in the Absence of Preclinical Efficacy Data

Abstract: Many animal models of disease are suboptimal in their representation of human diseases and lack of predictive power in the success of pivotal human trials. In the context of repurposing drugs with known human safety, it is sometimes appropriate to conduct the "last experiment first," that is, progressing directly to human investigations. However, there are not accepted criteria for when to proceed straight to humans to test a new indication. We propose a specific set of criteria to guide the decision-making ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…In this regard, our process presents the importance of complementing quantitative methods with qualitative evidence, as much of the contextual knowledge on obstetric prescriptive practice and pediatric disease assessment remains unavailable in structured databases. This combination of ML and consensus prioritization among human users for accurate outcomes analysis is archetypal of PheWAS and GWAS approaches, as many previous publications affirm 24 , 38 , 67 .…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, our process presents the importance of complementing quantitative methods with qualitative evidence, as much of the contextual knowledge on obstetric prescriptive practice and pediatric disease assessment remains unavailable in structured databases. This combination of ML and consensus prioritization among human users for accurate outcomes analysis is archetypal of PheWAS and GWAS approaches, as many previous publications affirm 24 , 38 , 67 .…”
Section: Discussionmentioning
confidence: 97%
“…The current analysis leverages the methods and experience of an experienced drug repurposing team; the methods employed have been developed and refined for generation of a number of repurposing opportunities across a variety of therapeutic candidates and conditions, as well as identification of potential safety signals associated with various agents ( 4 - 10 , 126 - 128 ). Further, the notable concordance between the PheWAS results and the primary literature provides additional confidence in the strength and validity of the identified connection between NAC and ALF.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we have demonstrated that the combination of PheWAS with thorough evidence review and synthesis can yield valuable and actionable insights regarding additional therapeutic uses of existing medicines ( 4 - 10 ). The current analysis applies these methods to one agent from the EML, N-acetylcysteine (NAC), currently listed for “exposure to or harmful effects of undetermined intent of analgesics, antipyretics, or NSAIDs (nonsteroidal anti-inflammatory drugs)”.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, our process presents the importance of complementing quantitative methods with qualitative evidence, as much of the contextual knowledge on obstetric prescriptive practice and pediatric disease assessment remains unavailable in structured databases. This combination of ML and consensus prioritization among human users for accurate outcomes analysis is archetypal of PheWAS and GWAS approaches, as many previous publications affirm 21,35,64 .…”
Section: Overall Limitations and Next Stepsmentioning
confidence: 95%